2021
DOI: 10.1038/s41598-021-88944-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between ACE2 and TMPRSS2 nasopharyngeal expression and COVID-19 respiratory distress

Abstract: ACE2 and TMPRSS2 are key players on SARS-CoV-2 entry into host cells. However, it is still unclear whether expression levels of these factors could reflect disease severity. Here, a case–control study was conducted with 213 SARS-CoV-2 positive individuals where cases were defined as COVID-19 patients with respiratory distress requiring oxygen support (N = 38) and controls were those with mild to moderate symptoms of the disease who did not need oxygen therapy along the entire clinical course (N = 175). ACE2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…In the study published by Lamers et al [ 34 ], a drop in ACE2 mRNA levels was observed in SARS-CoV2-infected human enterocytes at 24 h post-infection. This finding, which needs to be further replicated, is in line with previous reports obtained in SARS-CoV2-infected airway epithelial cells [ 57 , 58 ]. Authors from these studies and other researchers in the field proposed that the SARS-CoV2-induced dysregulation of ACE2 plays a major role in COVID-19 pathophysiology.…”
Section: Discussionsupporting
confidence: 92%
“…In the study published by Lamers et al [ 34 ], a drop in ACE2 mRNA levels was observed in SARS-CoV2-infected human enterocytes at 24 h post-infection. This finding, which needs to be further replicated, is in line with previous reports obtained in SARS-CoV2-infected airway epithelial cells [ 57 , 58 ]. Authors from these studies and other researchers in the field proposed that the SARS-CoV2-induced dysregulation of ACE2 plays a major role in COVID-19 pathophysiology.…”
Section: Discussionsupporting
confidence: 92%
“…A previous report showed that by binding to the ACE2 receptor in EC, spike causes the downregulation of ACE2 protein levels and the subsequent inhibition of mitochondrial function and eNOS activity leading to EC damage ( 9 ). Because ACE2 is anti-inflammatory ( 24 ), and its overexpression protects against severe COVID-19 symptoms ( 45 ) , spike-induced downregulation of ACE2 would cause inflammation to thrive. Paradoxically, we found that the spike activation of ⍺5β1-NF-κB signaling in ECs increases ACE2 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 and TMPRSS2 levels correlate with age and are strongly associated with respiratory distress. Increased nasopharyngeal ACE2 levels are protective and the TMPRSS2/ACE2 ratio is associated with risk of COVID-19 with prevalent symptomatology (cough, 70.42%; fever, 63.85%; headache, 61.50%; anosmia, 57.28%; myalgia, 55.87%) [212]. The imbalance between ACE1 and ACE2 activity is implicated in the pathogenesis of respiratory disorders and in COVID-19 severity.…”
Section: Covid-19mentioning
confidence: 99%